Pembelajaran Matematika Melalui Problem Based Learning dan Problem Posing Ditinjau dari Motivasi Belajar Matematika Siswa Kelas VIII - Puspasari, Friesta; , Rita P. Khotimah, S.Si., M.Sc; , Sri Rejeki, M.Pd, M.Sc (2015)
This study aims at evaluating: (1) the effect of students' mathematics learning achievement viewed from two different learning models, (2) the effect of students' mathematics learning achievement viewed from different level of learning motivation, (3) the effect of interaction between teaching models and learning motivation on students' mathematics learning achievement. This study is a quantitative research with a quasi-experimental research design. The population of this study is students of 8thgrade of SMP Negeri 1 Bergas. Two classes were chosen for the sample of this study by cluster random sampling. The first class was treated using Problem Based Learning (PBL) model and the second class was treated using Problem Posing model. The data collection was conducted using test, questionnaire, and documentation. The main data sources are the results of tests of learning achievement and questionnaire of learning motivation, while documents are used as additional data. Morever, the data was analized using different number of cell analysis of variance with 5% significante level. The conclusion are: (1) there is an effect on students' mathematics learning achievement viewed from two different learning models, (2) there is an effect on students' learning achievement viewed from different level of learning motivation, (3) there is no interaction between teaching models and learning motivation on students' mathematics learning achievement.